Qualitative Imbalance in Quantitative Growth: An Empirical Time Series Analysis of Korea’s Open Banking Platform - Gyongchan Chung (Platforms)
Despite remarkable quantitative growth in Application Programming Interface (API) call volume, Korea’s Open Banking Platform faces a critical qualitative imbalance. This paper investigates this hidden challenge, revealing a significant divergence between quantitative metrics and qualitative indicators. Through time-series analysis of registered accounts and user data, alongside examining financial institution and FinTech dynamics, I identify decelerating platform growth and constrained user base expansion. While API calls exploded, registered account and user growth lagged substantially. Platform growth exhibits player bias, and user base expansion has stagnated despite increased accounts-per-user ratios. These findings indicate that Korea’s Open Banking Platform’s sustainability is threatened by qualitative imbalances masked by quantitative success. I advocate for a shift to data-driven governance, moving beyond API call volume-centric metrics to qualitative indicators focused on user and account base assessment. I call for data-driven policy innovation to foster a more balanced and sustainable platform ecosystem, addressing growth slowdown and user base limitations.